Molecular Orbital Insights of Transition Metal-Stabilized Carbocations - Goodman, Hannah; Mei, Liangyong; Gianetti, Thomas L. (Frontiers in Chemistry, 2019)
Transition metal-stabilized carbocations are characterized by synthetically valuable interactions, yet there are no comprehensive reports of the many bonding modes that can exist between a metal and carbocation. This review summarizes developments in these metal complexes to provide a clear picture of their properties and reactivities; in order to strategically exploit them, we propose this summary of the different bonding modes for transition metal-carbocation complexes. These models will help chemists understand the orbital interactions involved in these compounds so that they can approach their synthetic goals most effectively. Multiple transition metals and carbocations will be discussed